Analysing and improving mathematical formulation of webavalia: a self and peer assessment tool - Babo, Rosalina (2022)
Recently, Problem-based learning has been increasingly used, and with those practices, self and peer evaluation tasks have gained more importance. This method of learning assists learners in the acquisition of skills and competencies. In order to support self and peer evaluation tasks, there are some different software offers in the market. The ease use of them is demanded since these tasks are an important part of evaluation. With the literature emphasis on the importance of assessment and critical spirit, it arises the possibility to implement formulas to increase the efficiency on the methodology applied and satisfaction of students and teachers. This paper introduces formulation problems about marks weighting in self and peer evaluation. It presents the advantages and disadvantages of different solutions for the formulation and suggestions of adapting them among tools, feedback surveys, and teacher’s methods of evaluation. It is also expected that the formulation, which was implemented in the software tool WEBAVALIA, has a great impact on feedback, improving user experience, and both efficiency and flexibility.